2015
DOI: 10.1039/c4an02316a
|View full text |Cite
|
Sign up to set email alerts
|

Certified ion implantation fluence by high accuracy RBS

Abstract: From measurements over the last two years we have demonstrated that the charge collection system based on Faraday cups can robustly give near-1% absolute implantation fluence accuracy for our electrostatically scanned 200 kV Danfysik ion implanter, using four-point-probe mapping with a demonstrated accuracy of 2%, and accurate Rutherford backscattering spectrometry (RBS) of test implants from our quality assurance programme. The RBS is traceable to the certified reference material IRMM-ERM-EG001/BAM-L001, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…This calibration method has been validated at both universities of Surrey and Namur by comparison to other calibration methods: namely, the 27 Al(p,) 28 Si resonant reaction [1] & the non-resonant 16 O(p,γ) 17 F proton capture [3] at Surrey, and the use of a triple-alpha source [7,8] at Surrey & Namur. We will show that these new measurements enable us to significantly reduce the uncertainty on the position of this 16 O() 16 O resonance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This calibration method has been validated at both universities of Surrey and Namur by comparison to other calibration methods: namely, the 27 Al(p,) 28 Si resonant reaction [1] & the non-resonant 16 O(p,γ) 17 F proton capture [3] at Surrey, and the use of a triple-alpha source [7,8] at Surrey & Namur. We will show that these new measurements enable us to significantly reduce the uncertainty on the position of this 16 O() 16 O resonance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the standard calibration points such as the important 27 Al(p,) 28 Si resonant reaction at 992 keV [1] or neutron thresholds such as the 7 Li(p,n) 8 Be at 1881 keV [2] are mostly for a proton beam at various energies. Analysts using an alpha beam (for an enhanced depth resolution) have not conveniently been able to verify their energy calibration.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows spectra taken from our programme for the quality assurance (QA) of our quantitative implantation, which is discussed in detail elsewhere 2 . The statistics in these spectra are very good since the signals of interest are rather small and we want a 1% measurement accuracy.…”
Section: Y = Q  / []mentioning
confidence: 99%
“…We have recently demonstrated that high accuracy RBS can be used for validating the accuracy of our implanted fluence measurement both by charge collection and also by sheet resistance measurements 1,2 . This is an important result showing that RBS and quantitative implantation are both suitable for certifying new ion implanted or other standards for the quantification of other analytical techniques such as secondary ion mass spectrometry (SIMS) or Xray fluorescence (XRF).…”
Section: Introduction: the Value Of High Accuracy Rbsmentioning
confidence: 99%
See 1 more Smart Citation